PENGARUH VARIASI PENYAJIAN MAKANAN TERHADAP PERSEPSI PENAMPILAN DAN DAYA TERIMA MAKANAN PADA PASIEN ANAK DI RSUD BANYUMAS - Shanty Triastuti; Ana Yuliah Rahmawati; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2017)
Background: The remaining food of pediatric patients in the inpatient ward of RSUD Banyumas is still high. In addition, factors related to patient satisfaction are influenced by the appearance of food and how the presentation. Factors that can be used as an enhanced presentation of interest include color, texture, color, large portions, serving and decking of food. One effort to improve the patient's child's acceptance of the food served is to serve an interesting meal. Modification of the shape and appearance of food when presented can attract attention so that children are interested to eat and want to spend the food served.Objective: Knowing the effect variation of food serve to appear perception and acceptance food for children patients in RSUD BanyumasResearch Method: This Research is a kind of experiment with planning of Quasy Experimental. The amount subject of the research is 48 people who have some criteria inclusion. The data included perception of food appearance and food acceptance using Comstock. The statistical test used is chi Square.Results: The patient's perception of the food appearance was satisfactorily varied at 87.5%. The acceptance of feeding patients given food presentation was varied by 41.7%. There is influence of variation of food presentation to perception of appearance in pediatric patient with p value 0.000. There was no effect of variation of food presentation on patient's pediatrics, with p value 0.221.Conclusion: Variations in food presentation affect the respondent's perception of the appearance of the food served, but it does not affect the acceptance.